Effect of Black Soybean Substitution and Fermentation Method (Backslope vs. Precision) on the Physical and Sensory Properties of Symbiotic Yogurt Ice Cream - Adelya Desi Kurniawati; Fenty Nurtyastuti Eka Pertiwi; Muhammad Dary Amjad; Lintang Lisinanda Cahyaning Putri; Dwi Astuti Aprilina; Titis Sari Kusuma; Yosfi Rahmi (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2025)
The development of symbiotic frozen desserts using locally sourced plant-based ingredients remains limited, particularly the use of Indonesian Detam-1 black soybean and the comparison of different yogurt fermentation methods. This study aimed to formulate symbiotic yogurt ice cream by substituting whole cream milk with Detam-1 black soybean paste (0%, 10%, 20%) and applying two fermentation approaches: backslope and precision. A Completely Randomized Design with three replications was used. Physical evaluations included measurements of viscosity, overrun, total soluble solids, and melting time, while sensory analysis involved 40 semi-trained panelists using a nine-point hedonic scale. Data were analyzed using two-way ANOVA followed by Duncan’s test. The results showed that the fermentation method had no significant effect on any of the parameters (p > 0.05). The best physical performance was observed in the 20% substitution formula (F2), which showed the highest viscosity and a melting time of around 31 minutes for both methods. Although increasing substitution levels slightly reduced preference, the product’s overall appearance maintained a neutral to like moderately range (5.78 to 6.70). These findings indicate that Detam-1 black soybean paste has strong potential as a functional, locally plant-based prebiotic source and provides new insight into the comparative use of backslope versus precision fermentation in symbiotic frozen dessert development.